2012
DOI: 10.1002/14651858.cd007162.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Knee length versus thigh length graduated compression stockings for prevention of deep vein thrombosis in postoperative surgical patients

Abstract: This review found that there is insufficient high quality evidence to determine whether or not KL and TL GCS differ in their effectiveness in terms of reducing the incidence of deep vein thrombosis (DVT) in hospitalised patients.  A major multicentre RCT is required to address this issue. In the meantime, the decision on which type of stocking to use in clinical practice is likely to be influenced by factors such as patient compliance, ease of use and cost implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
21
0
3
Order By: Relevance
“…62 A larger Cochrane study that compared thigh-length to calf-length intermittent pneumatic compression devices for deep venous thrombosis prevention in surgical patients showed no significant difference in deep venous thrombosis. 63 Although one metaanalysis 57 suggested that elastic stockings plus a second method of prophylaxis is superior to elastic stockings alone, the combination of intermittent pneumatic compression plus elastic stockings compared to other means of intermittent pneumatic compression alone was not explicitly studied. Therefore, a recommendation of adding elastic stockings to intermittent pneumatic compression cannot be made for plastic surgery patients.…”
Section: Recommendationmentioning
confidence: 99%
“…62 A larger Cochrane study that compared thigh-length to calf-length intermittent pneumatic compression devices for deep venous thrombosis prevention in surgical patients showed no significant difference in deep venous thrombosis. 63 Although one metaanalysis 57 suggested that elastic stockings plus a second method of prophylaxis is superior to elastic stockings alone, the combination of intermittent pneumatic compression plus elastic stockings compared to other means of intermittent pneumatic compression alone was not explicitly studied. Therefore, a recommendation of adding elastic stockings to intermittent pneumatic compression cannot be made for plastic surgery patients.…”
Section: Recommendationmentioning
confidence: 99%
“…These studies showed no significant difference in the ability of the two modalities of leg compression to reduce the incidence of deep vein thrombosis in post-operative patients. In both, the fixed-effect model (OR 1.55, 95 % CI 0.78-3.07, p = 0.21) and random-effects model (OR 1.32, 95 % CI 0.43-4.06, p = 0.63) [12]. In the absence of evidence to support benefit of thigh length over knee length graduated compression, the use of knee length garments in clinical practice is driven by factors such as ease of application, lower cost, and increased compliance by patients.…”
Section: Graduated Compression Stockingsmentioning
confidence: 93%
“…22 Another meta-analysis compared the effectiveness of knee length and thigh length GCSs in hospitalized patients for DVT prevention; those researchers concluded that the evidence was insufficient to determine if one length was superior to another in reducing the incidence of DVT. 33 A systematic review was done to evaluate the efficacy of IPCDs and VFPs for DVT prevention in adult trauma patients, and the researchers reported that although both IPCDs and VFPs reduced the incidence of DVT, VFPs were more effective. 23 In a prospective cohort study, 26 researchers examined the association of IPCDs and GCSs and VTE prevention in critically ill medical-surgical patients and reported that IPCDs were associated with a significantly lower risk of VTE but GCSs were not.…”
Section: Supporting Evidencementioning
confidence: 99%